2020
DOI: 10.31482/mmsl.2020.016
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Awareness in Kuwaiti Hospitals

Abstract: As of 14 th July 2020, 12,964,809 confirmed cases of coronavirus (COVID-19) and 570,288 deaths had been reported globally. In Kuwait, the numbers stood at 55,508 confirmed cases and 393 deaths. The disease seems to be hitting hard on the country despite the measures that have been put in place. The current study sought to examine healthcare workers HCWs awareness and perceptions of coronavirus disease in Kuwait hospitals. A prospective study design was used to examine the development of the disease among 28 HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This result is supported by other studies, one study conducted by Alshammari et al who aimed to assess HCWs awareness and perceptions of COVID in Kuwait hospitals where they included 28 HCWs, another study by Acharya et al who aimed to assess the KAP of Nepali medical and dental practitioners on infection control during the COVID-19 pandemic through an online circulated questionnaire, and one more conducted by Bhagavathula et al who conducted a survey among 453 HCWs to asses knowledge and perceptions towards COVID-19 infection where almost all of the participants in the three studies were knowledgeable that hand hygiene, covering the nose and the mouth while coughing reduces the risk of transmission of COVID-19 infection. It is worth noting that this high level of knowledge regarding prevention of COVID-19 infection would help in combatting the current pandemic among HCWs in particular and the public in general [30], [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…This result is supported by other studies, one study conducted by Alshammari et al who aimed to assess HCWs awareness and perceptions of COVID in Kuwait hospitals where they included 28 HCWs, another study by Acharya et al who aimed to assess the KAP of Nepali medical and dental practitioners on infection control during the COVID-19 pandemic through an online circulated questionnaire, and one more conducted by Bhagavathula et al who conducted a survey among 453 HCWs to asses knowledge and perceptions towards COVID-19 infection where almost all of the participants in the three studies were knowledgeable that hand hygiene, covering the nose and the mouth while coughing reduces the risk of transmission of COVID-19 infection. It is worth noting that this high level of knowledge regarding prevention of COVID-19 infection would help in combatting the current pandemic among HCWs in particular and the public in general [30], [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…Around 43% of the participants were uncertain about the symptoms of COVID-19 and surprisingly almost half of the participants were not aware of skin rash as a symptom of COVID-19. From the literature a study found that 32.1% could not identify skin rashes as a symptom related to covid-19 (Alshammari et al, 2020). Moreover, some healthcare professionals reported the availability of a vaccine.…”
Section: Perceptions About Covid-19mentioning
confidence: 99%
“…Recent research was conducted to measure the awareness and understanding of healthcare professionals about COVID-19. However, the research used a small sample size compared to similar research, indicated that the outcome must be interpreted with caution (Alshammari et al,2020). With the above literature in mind, the aim of this study was to investigate healthcare professionals' knowledge and perceptions about COVID-19 in two Arabian gulf countries -Saudi Arabia and Kuwait.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations